2005
DOI: 10.1002/pca.802
|View full text |Cite
|
Sign up to set email alerts
|

Identification by HPLC‐PAD‐MS and quantification by HPLC‐PAD of phenylethanoid glycosides of five Phlomis species

Abstract: The qualitative and quantitative determination of phenylethanoid glycosides in methanolic extracts of five species of the genus Phlomis (Lamiaceae) has been investigated using a new reversed-phase HPLC method combined with photodiode-array detection and electrospray/MS analysis. Forsythoside B, verbascoside, samioside, alyssonoside, isoverbascoside, leucosceptosides A and B and martynoside were detected. The quantification of the above constituents was performed using echinacoside as internal standard. Knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 14 publications
9
40
1
1
Order By: Relevance
“…russeliana and P. kurdica, demonstrated that variations in the content of PhGs can be used for chemotaxonomical study within the same genus [141]. Other studies have also confirmed the utilization of PhGs as taxonomic markers of genus Orobanche [142], Sibthorpia, and Ellisiophyllum (Plantaginaceae) [143].…”
Section: Chemotaxonomymentioning
confidence: 68%
“…russeliana and P. kurdica, demonstrated that variations in the content of PhGs can be used for chemotaxonomical study within the same genus [141]. Other studies have also confirmed the utilization of PhGs as taxonomic markers of genus Orobanche [142], Sibthorpia, and Ellisiophyllum (Plantaginaceae) [143].…”
Section: Chemotaxonomymentioning
confidence: 68%
“…The MS spectrum of compound 3, identified as caffeic acid, reported a quasimolecular ion [M+H] (163 m/z). Compound 1, with the presence of caffeoyl group (163 m/z), was identified as forsythoside B, previously reported in literature in the genus Phlomis [16]. The antioxidant properties of the plant, as well as some of its traditional uses, may be related to this phenylpropanoids.…”
Section: Bioassay-guided Isolation Of Antioxidant Phenylpropanoidsmentioning
confidence: 93%
“…These phenylpropanoids (Fig. 3) have been described in other Phlomis species [3,16,[30][31][32][33][34][35][36], considered as Fig. 3 HPLC-DAD chromatographic profile of subfraction F4-6 at 330 nm and UV-vis spectra of compounds chemotaxonomic markers and reported as radical scavengers [37].…”
Section: Bioassay-guided Isolation Of Antioxidant Phenylpropanoidsmentioning
confidence: 99%
See 2 more Smart Citations